Editorial - Rojas Herrera, María Elena (Cooperativismo & Desarrollo, 2023)
The articles present diverse and original topics, showing a mosaic of the practice of SSE in Mexico. One of them delves into theoretical reflection through a bibliometric analysis of scientific production on agricultural cooperatives in Spanish-speaking countries, while the others present the results of research carried out with organizations from four states of the territory (Hidalgo, Tlaxcala, Oaxaca and Chiapas). . These studies reflect the analytical efforts of the authors and are characterized by giving voice to the subjects investigated, through argumentation supported by testimonies from the actors themselves and through the practice of dialogue of knowledge between the researchers and the communities studied. Without a doubt, the value and significance of these works lies in making the ESS organizations visible. The set of articles contributes to the development of research, documentation and dissemination, to the extent that they can be a reference for future studies.